Vaginal paraurethral leiomyoma - Bijwe, Smita Anand; Deshmukh, Anil T.; Tanya, Srishti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Leiomyomas of the vagina are uncommon soft tissue tumors. Only a few cases are reported in medical literature. It is usually seen between 20-80 years of age. We report a case of 30-year-old woman with paraurethral leiomyoma. Leiomyomas in this location should be differentiated from urethral diverticula and vaginal cysts. Complete surgical excision should be the choice of treatment. Excision usually has good prognosis and rarely recurs.